A review of progress in (bio)catalytic routes from/to renewable succinic acid. (14th June 2017) - Mazière, Audrey; Prinsen, Pepijn; García, Araceli; Luque, Rafael; Len, Christophe
Abstract: In the last decade, succinic acid has become a key platform chemical in the bio‐based industry. It is one of the few renewable chemicals that have proven to be competitive with the fossil‐derived production. Still, improvements can be made in terms of sustainability, especially in the usage of alternative carbon sources for advanced life cycles. Numerous catalytic routes have been developed for the conversion of bio‐succinate to a wide range of chemical compounds and bio‐based polymers. However, most of them have been demonstrated from pure isolated succinic acid, but the isolation and purification of succinic acid from fermentation broths is no mean task and requires a considerable amount of energy. Therefore, catalytic routes in aqueous phase have also been studied intensively to by‐pass isolation and purification steps. This review describes the recent developments published in this research field. © 2017 Society of Chemical Industry and John Wiley & Sons, Ltd